Stent for Life Initiative: leading example in building STEMI systems of care in emerging countries - Kaifoszova, Zuzana; Kala, Petr; Alexander, Thomas; Zhang, Yan; Huo, Yong; Snyders, Adriaan; Delport, Rhena; Alcocer-Gamba, Marco Antonio; Gavidia, Leslie Marisol Lugo (EuroIntervention, 2014)
This paper describes the opportunities and challenges in building ST-elevation acute myocardial infarction (STEMI) systems of care in Stent for Life affiliated and collaborating so-called emerging countries, namely India, China, South Africa and Mexico, where CAD mortality is increasing and becoming a significant healthcare problem. The Stent for Life model supports the implementation of ESC STEMI Guidelines in Europe and endeavours to impact on morbidity and mortality by improving services and developing regional STEMI systems of care, whereby STEMI patients' timely access to a primary percutaneous coronary intervention (PPCI) is assured. In India, the STEMI India model incorporates a dual approach of combining PPCI with a pharmacoinvasive strategy of reperfusion. The architecture of the system is based on a hub and spoke model with each unit called a STEMI cluster. The project is driven by a private non-profit organisation. In China, the STEMI PCI programme is led by the Chinese College of Cardiovascular Physicians and supported by the national government. Although primary PCI is performed nationwide, a thrombolytic treatment strategy is still the first option in many rural areas because of logistic considerations. Establishing local STEMI transfer networks and then implementing a pharmacoinvasive strategy of reperfusion are being considered and promoted currently. In South Africa, the pharmacoinvasive approach currently dominates as STEMI treatment option in many areas. A pilot study shows that low symptom awareness leads to long patient delays. The education of all role players, from patients to healthcare professionals and including institutions and governmental structures, is needed to achieve prompt diagnosis and treatment. In Mexico, improving the treatment of STEMI requires considering myocardial infarction to be an emergency that must be treated by an entire system and not just by a particular service. Patients need to receive quick treatment from clinical and interventional cardiologists, and the emergency medical system (EMS) must understand the importance of early reperfusion therapy when appropriate. Mexican health authorities have used registries as their main strategy for improving the use of health resources for ACS patients. In general, building regional STEMI systems of care and an EMS system infrastructure are critical success factors in the stepwise development of STEMI systems of care at a national level in emerging countries as they are in Europe. An in-depth understanding of healthcare system-level barriers to timely and appropriate reperfusion therapy facilitates the development of more effective strategies for improving the quality of STEMI care in each region and country.
Keywords: Myocardial Infarction; stenty; urgentní zdravotnické služby; Percutaneous Coronary Intervention; reperfuze myokardu; Europe; Stents; Humans; Myocardial Reperfusion; lidé; Delivery of Health Care; infarkt myokardu; koronární angioplastika; Evropa; Emergency Medical Services; poskytování zdravotní péče